Deep Learning Analysis of Skeletal Muscle Gene Expression and Splicing in Exercise-Induced Metabolic Adaptation - Hanfei Wei (International Journal of Clinical and Translational Medicine, 2026)
Skeletal muscle is a highly plastic tissue that orchestrates systemic metabolic adaptation to exercise through coordinated changes in gene expression and alternative splicing. The complexity of these regulatory layers has historically outstripped the analytical capacity of conventional bioinformatics, but the advent of deep learning architectures is transforming the study of exercise‑induced transcriptomic remodeling. This paper presents a system‑level analysis of how deep neural networks can be leveraged to model the interplay between gene expression and splicing in human skeletal muscle during metabolic adaptation. We examine the architectural choices—ranging from convolutional and recurrent networks to attention‑based transformers—that are particularly suited for capturing the sequence grammar of splicing and the dynamic patterns of expression. Beyond algorithm design, the paper addresses the infrastructure, data governance, and scalability challenges that arise when building large‑scale, multi‑omic data commons for exercise genomics. We discuss how federated learning, differential privacy, and fairness‑aware model design can mitigate the risks of population bias and inequitable precision health outcomes. The integration of proton‑sensing molecular reporters, transcriptomic deep learning, and metabolic phenotyping is explored as a frontier for capturing the ionic‑stress dimension of exercise physiology. The analysis further evaluates the translational implications of these models for personalized exercise prescription and the policy frameworks required to ensure equitable access, algorithmic transparency, and long‑term sustainability of AI‑driven metabolic health infrastructure. Throughout, we emphasize structural trade‑offs between model complexity and interpretability, the robustness of splicing predictions across ancestrally diverse cohorts, and the ethical responsibilities that accompany the deployment of deep learning in health‑related behavioral interventions.